Origin and evolution of the South Carpathians basement (Romania): a zircon and monazite geochronologic study of its Alpine sedimentary cover. Issue 4 (11th March 2016) - Stoica, Adriana M.; Ducea, Mihai N.; Roban, Relu D.; Jianu, Denisa
Abstract: This study investigates the advantages of a multi-mineral approach in detrital mineral geochronology, as tracers of regional tectonic events. We present new detrital zircon and monazite ages on six sands and sandstones collected from the South Carpathians, Romania. They represent clastic sediments derived from the pre-Alpine basement and related sedimentary cover, which accumulated in distinct palaeogeographic and geotectonic environments, during the multiphase Alpine tectonic evolution. Three samples are mid-Cretaceous sandstones from different depositional settings of the syn-tectonic clastic wedge that activated during the intra-Albian thrusting phase. One is Upper Cretaceous sandstone from the South Carpathian foredeep, associated with the intra-Maastrichtian thrusting phase. Two additional samples are Quaternary fluvial deposits reworking the Upper Cretaceous hinterland basin siliciclastic deposits. Detrital zircon U–Pb ages confirm periods of zircon-producing magmatism in the Neoproterozoic (ca. 590–850 Ma), Cambrian–Ordovician (ca. 540–450 Ma), and, in one sample, Late Cretaceous (ca. 76–81 Ma). Precambrian tectonics is documented by inherited zircons (ca. 0.9–1.2 Ga, 1.8–2.2 Ga, 2.6–2.8 Ga), most likely recycled from metasedimentary rock units from the Getic basement. Zircon age distribution patterns from all samples are consistent with derivation from eroded equivalents to basement rocks of the Getic–Supragetic thrust sheets. In contrast, chemical ages on all detrital monazites document a single metamorphic event of Late Devonian to Carboniferous ages (ca. 300–400 Ma), coincident with the Variscan orogeny in central Europe. A small proportion of the zircon population is also of the same age range (ca. 380–320 Ma) – those zircons typically have high U–Th ratios, characteristic of metamorphic zircons. Detrital monazite ages are consistent with previous limited geochronological data on high-pressure metamorphic rocks from the Getic–Supragetic basement. In addition to the timing of tectonic events in the Carpathian basement, geochronology of detrital minerals brings new constraints regarding the duration of these events.